Açık Erişim - Ziya Kutluoğlu (Türk Kütüphaneciliği)
Latest situation of open access has been summarized in the editorial in consideration of 3rd National Open Access Workshop also commends of 60th establishment anniversary of Ankara University Department of Information and Records Management, result of TLA general meeting and some commends regarding current employment ratio of librarians in Turkey.